The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41467-022-33679-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assembly, positioning and contraction of a division ring in minimal cells

Abstract: Constructing a minimal machinery for autonomous self-division of synthetic cells is a major goal of bottom-up synthetic biology. One paradigm has been the E. coli divisome, with the MinCDE protein system guiding assembly and positioning of a presumably contractile ring based on FtsZ and its membrane adaptor FtsA. Here, we demonstrate the full in vitro reconstitution of this machinery consisting of five proteins within lipid vesicles, allowing to observe the following sequence of events in real time: 1) Assembl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 67 publications
1
55
1
3
Order By: Relevance
“…The temperature-induced contraction would in principle be compatible with liposome-encapsulation and the contraction force could potentially be sufficiently high to induce vesicle deformation ( 23 ). It could be complemented by engineered molecular motors that walk on DNA nanotubes ( 25 ). For ring disassembly, which will be necessary to complete the division of the compartment, it is plausible to use mechanisms that have already been described for DNA nanotubes ( 11, 12, 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature-induced contraction would in principle be compatible with liposome-encapsulation and the contraction force could potentially be sufficiently high to induce vesicle deformation ( 23 ). It could be complemented by engineered molecular motors that walk on DNA nanotubes ( 25 ). For ring disassembly, which will be necessary to complete the division of the compartment, it is plausible to use mechanisms that have already been described for DNA nanotubes ( 11, 12, 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…10(e) and (f)). 78 In addition, other protein systems, for example, bundled actin filaments, can also be used to construct contractile actomyosin rings in liposomes to govern the vesicle shapes. 79 Alternatively, the endosomal sorting complex required for transport (ESCRT) proteins which form a multicomplex sorting machinery that controls multivesicular body formation in vivo, can also induce budding and complete division of GUVs.…”
Section: Protein-mediated Divisionmentioning
confidence: 99%
“…Cell-free expression systems have been crucial in bottom-up synthetic biology, and have an enormous potential to be further utilized in various experimental setups by proper choice and optimization of the configuration, such as cell types and cell lysate or purified components-based systems. In this study, we chose the E. coli -based cell-free synthesis platform called PURE system ( 35 ), because it has been demonstrated that the PURE system can synthesize Min proteins, and that such cell-free expressed MinD and MinE proteins can self-organize into dynamic wave patterns in vitro in cell-mimicking environments such as lipid containers ( 36, 37 ).…”
Section: Mainmentioning
confidence: 99%